Sustainable silk yarn dyeing using Hibiscus rosa-sinensis: optimisation of process variables via response surface methodology approach - Wan Mohd Juhari, Wan Azwin Idayu; Wan Abdul Khodir, Wan Khartini; Abdul Jalal, Ahmad Farid; Abd Hamid, Shafida (Institut Kimia Malaysia, 2025)
Natural dyes offer an eco-friendly alternative to synthetic dyes, aligning with sustainable textile practices. This study aimed to evaluate the potential of Hibiscus rosa-sinensis flower extract as a natural dye for silk yarn and to optimise its dyeing parameters. H. rosa-sinensis natural dye was extracted using an acidified (4% citric acid) water extraction method, which was used to dye the silk yarn. The dyeing parameters, including pH, temperature, weight/volume ratio, and dyeing duration were evaluated using Response Surface Methodology (RSM). The optimum dyeing conditions were determined at pH 3, 30 °C, for 30 minutes, and a weight/volume ratio of 0.06 g/mL, resulting in a colour intensity of 30.35. The experimental outcomes were consistent with the predicted colour intensity of 32.05, confirming the reliability of the optimised parameters. The study further explored the effects of pH on the hue of the dyed yarn, showing a vibrant red at pH 3, which gradually shifted to greenish-brown at higher pH. The UV-visible spectrometry confirmed the stability of the anthocyanin pigments at lower pH levels. The findings demonstrate the potential of H. rosa-sinensis as a sustainable dye and provide insights into optimising parameters for natural dyeing processes. Future research could expand on using other mordants and explore co-pigmentation strategies to enhance dye stability and colour properties